A whole new ballgame: an analysis of the context and adoption of long-term athlete development in community sport. Issue 4 (4th July 2022) - Jurbala, Paul; Stevens, Julie
ABSTRACT: Rationale/Purpose: The purpose of this study was to explore the context for innovation and how it ultimately affected sport club decisions to adopt Long-Term Athlete Development (LTAD). Design/methodology/approach: Interview and documentary data were gathered from Canadian sport clubs and provincial sport organizations implementing LTAD, an initiative intended to improve the quality of sport programs. Following a critical realist framework, a retroductive grounded theory approach was used to identify themes and structural mechanisms influencing club decisions to adopt. Findings: LTAD adoption generated internal conflict for clubs while creating opportunity for competition with rivals. Resource and institutional pressures both enabled and inhibited innovation. Clubs pursued innovation when resource controllers signaled that increased legitimacy would result. Clubs with capacity to adopt used LTAD as a means to maintain or improve their competitive position. Practical implications: Policies promoting community sport adoption of innovations to improve program quality may create thresholds allowing clubs with capacity to adopt the opportunity to out-perform or eliminate rivals. This may paradoxically result in increased costs and/or diminished access to sport for participants. Research Contribution: This provides new insight into how community sport clubs manage conflicting logics and compete through compliance with the policies of resource controllers. A contextual model of community sport club operation under conflicting logics is presented.